Effects of acute Salbutamol inhalation on quadriceps force and fatigability - Decorte, N.; Verges, S.; Flore, P.; Guinot, M.; Wuyam, B. (Medicine & Science in Sports & Exercise, 2008)
Introduction: Oral beta2-agonist administration improves muscle function in persons without asthma. We performed a double-blind, randomized, controlled crossover study to assess whether acute inhaled salbutamol administration improves muscle strength and fatigability in healthy moderately trained subjects.